Anti‐Inflammatory Effects of the Flowers of Prunus persica var. davidiana. Issue 2 (8th December 2015) - Tettey, Clement O.; Lincha, Victor R.; Lee, Dong‐Ung; Yang, In‐Jun; Shin, Heung‐Mook
Abstract: The crude methanolic P runus persica var. davidiana ( P . persica var. davidiana ) flower extract was subsequently fractionated versus hexane, methylene chloride, ethyl acetate, and butanol and their potential in vitro anti‐inflammatory effects investigated. The hexane and methylene chloride extracts were withdrawn from the study because they were toxic. The methanolic, ethyl acetate and butanol extracts significantly suppressed the Lipopolysaccharide (LPS)‐induced nitric oxide (NO) production as well as inducible nitric oxide synthase (iNOS) mRNA expressions. mRNA and protein levels of cyclooxygenase (COX)‐2 were also significantly inhibited by all three extracts relative to the LPS‐treated group. However, only the ethyl acetate fraction reduced prostaglandin E (PGE)2 levels appreciably. All three extracts significantly suppressed interleukin (IL)‐1β protein expression but had no effect on the LPS‐induced TNF‐α and IL‐6 protein levels. The mRNA expressions of tumor necrosis factor (TNF)‐α, IL‐1β and IL‐6 were also significantly suppressed, except for the ethyl acetate fraction, which had no appreciable effect on IL‐6 mRNA. Moreover, the LPS‐induced phosphorylations of c‐Jun N‐terminal kinase (JNK)‐1 and extracellular signal‐regulated kinase (ERK)1/2 were significantly suppressed by the three extracts, whereas the butanol fraction had no effect on p‐P38 expression. The results of this study demonstrate that the crude methanolic extract (M) of P . persica flowers and the ethyl acetate (E) and butanol (B) fractions possess significant anti‐inflammatory activities and have potential as leads for the discovery of anti‐inflammatory phytocompounds. Practical Applications: Inflammation is implicated in a good number of diseases. Chronic and uncontrolled inflammation results in several malignancies, necessitating the need for adequate treatment. The present study exhibits the in vitro efficacy of fractionated P . persica flower extracts against inflammation. The result of this study should be applied in the extraction of leads and further development of inflammatory drugs of natural origin to obviate the noxious effect of current synthetic pharmaceuticals.